Nanopatterning of steel by one-step anodization for anti-adhesion of bacteria - Shiqiang Chen (Nature Portfolio, 2017)
Abstract Surface nanopatterning of metals has been an effective technique for improved performance and functionalization. However, it is of great challenge to fabricate nanostructure on carbon steels despite their extensive use and urgent needs to maintain the performance reliability and durability. Here, we report a one-step anodization technique to nanopattern a carbon steel in 50 wt.% NaOH solution for highly effective anti-adhesion by sulphate reducing bacteria (SRB), i.e., Desulfovibrio desulfuricans subsp. desulfuricans (Beijerinck) Kluyver and van Niel. We characterize the morphology, structure, composition, and surface roughness of the nanostructured film formed on the steel as a function of anodizing potential. We quantify the surface hydrophobicity by contact angle measurements, and the SRB adhesion by fluorescent analysis. The optimal anodization potential of 2.0 V is determined for the best performance of anti-adhesion of SRB to the steel, resulting in a 23.5 times of reduction of SRB adhesion compared to bare steel. We discuss the mechanisms for the film formation on the steel during anodization, and the high-performance anti-adhesion of bacteria to nanopatterned steels. Our technique is simple, cost-effective and environment-friendly, providing a promising alternative for industry-scale surface nanopatterning of carbon steels for effective controlling of bacterial adhesion.